Evaluation of Water Access Sanitation and Hygiene CSR Program By Danone AQUA (Case Study in Nanggareng Village - Pratama, Irsyad Wicaksono; Rudito, Bambang (Journal of Business and Management, 2012)
Indonesia is one of developing countries in the world. Developing countries usually face some common challenge that is economic crisis, the lack of education among poor communities, even environmental problems. Environmental problems could be depends on the geographic condition in every country, which such as draught, climate change problems, pollution, and the lack of clean water that considered being one of few main problems that exist in every developing country around the world, especially in Nanggerang village, Sukabumi, West Java, Indonesia. The lack of water system and sanitation became a vital problem for Nanggerang village from a long time. This problem made quite impacts for Nanggerang village community in their daily life, economic and environmental condition. From the economic aspect, the efficiency and effectively of their efforts on getting clean water affect their daily expense and very time consuming. From the environment aspect, because the lack of clean water in almost every toilet in each houses in Nanggerang.Water Access Sanitation and Hygiene (WASH) program which initiated by Nanggerang village community and DANONE Aqua with the help from YPCII (Yayasan Pembangunan Cintra Insan Indonesia), Departemen Pekerjaan Umum, and Pemerintah Daerah Kabupaten Sukabumi, has help Nanggerang Village to fight their water and sanitation problem. Based on the evaluation of the research and condition from Nanggerang village community, we can take a conclusion that the implementation of WASH program on Nanggerang village has become very successful.Keywords:Â Corporate Social Responsibility, Sustainable Development, and Community DevelopmentÂ